PENERAPAN PRINSIP-PRINSIP MANAJEMEN DALAM KEPEMIMPINAN DI SEKOLAH MENENGAH PERTAMA MAN ANA PAMIJAHAN KABUPATEN BOGOR PROVINSI JAWA BARAT - Akmal Ihsanudin Rabbani Al-Shidqi; Pitri Rahayu (Jurnal Pijar, 2026)
The main study in this research is the application of management principles in leadership at Man Ana Pamijahan Junior High School. The population was taken from the elements of permanent teachers and educational staff with a population of 30 people, a sample of 12 people was determined using the saturated sample technique. This type of research is descriptive quantitative. Data were collected through technical observation, literature, and questionnaires. Data processing was measured using five Likert scales according to Sugiyono which had been modified by researchers. The results of the study show that the leadership of Man Ana Junior High School has implemented the fourteen management principles according to Henry Fayol. The average of each indicator is included in the “Applied” criteria. One indicator namely; Fairness and Honesty are included in the "Highly Applied" criteria, while 13 other indicators are included in the "Applied" criteria. The leadership of Man Ana Pamijahan Junior High School which highly upholds Morals and Ethics has proven that the principles of justice towards others and honest attitude in behavior are things that must be highly applied in living life and school management, this is in accordance with the first Motto of Man Ana Pamijahan Middle School namely "Having Noble Moral" and according to the results of the research from the attitude of the respondents who rated 81% so that it was included in the "Highly Applied" criteria